Organ tropism of Sendai virus in mice: proteolytic activation of the fusion glycoprotein in mouse organs and budding site at the bronchial epithelium. - Tashiro, M (1990)
Wild-type Sendai virus is exclusively pneumotropic in mice, while a host range mutant, F1-R, is pantropic. The latter was attributed to structural changes in the fusion (F) glycoprotein, which was cleaved by ubiquitous proteases present in many organs (M. Tashiro, E. Pritzer, M. A. Khoshnan, M. Yamakawa, K. Kuroda, H.-D. Klenk, R. Rott, and J. T. Seto, Virology 165:577-583, 1988). These studies were extended by investigating, by use of an organ block culture system of mice, whether differences exist in the susceptibility of the lung and the other organs to the viruses and in proteolytic activation of the F protein of the viruses. Block cultures of mouse organs were shown to synthesize the viral polypeptides and to support productive infections by the viruses. These findings ruled out the possibility that pneumotropism of wild-type virus results because only the respiratory organs are susceptible to the virus. Progeny virus of F1-R was produced in the activated form as shown by infectivity assays and proteolytic cleavage of the F protein in the infected organ cultures. On the other hand, much of wild-type virus produced in cultures of organs other than lung remained nonactivated. The findings indicate that the F protein of wild-type virus was poorly activated by ubiquitous proteases which efficiently activated the F protein of F1-R. Thus, the activating protease for wild-type F protein is present only in the respiratory organs. These results, taken together with a comparison of the predicted amino acid substitutions between the viruses, strongly suggest that the different efficiencies among mouse organs in the proteolytic activation of F protein must be the primary determinant for organ tropism of Sendai virus. Additionally, immunoelectron microscopic examination of the mouse bronchus indicated that the budding site of wild-type virus was restricted to the apical domain of the epithelium, whereas budding by F1-R occurred at the apical and basal domains. Bipolar budding was also observed in MDCK monolayers infected with F1-R. The differential budding site at the primary target of infection may be an additional determinant for organ tropism of Sendai virus in mice.